Co(II) Amide, Pyrrolate, and Aminopyridinate Complexes: Assessment of their Manifold Structural Chemistry and Thermal Properties. Issue 48 (12th November 2021) - Zanders, David; Boysen, Nils; Land, Michael A.; Obenlüneschloß, Jorit; Masuda, Jason D.; Mallick, Bert; Barry, Seán T.; Devi, Anjana
Abstract: A series of cobalt(II) (silyl)amides, pyrrolates and aminopyridinates were synthesized. Inspired by the dimeric bis(trimethylsilylamido)cobalt(II) complex ([Co(TMSA)2 ]2 ), facile salt metathesis employing the ligand 2, 2, 5, 5‐tetramethyl‐1, 2, 5‐azadisilolidinyl (TMADS) yielded its congener [Co(TMADS)2 ]2 . Novel, heteroleptic Lewis adducts of the former resulted in unusual three‐ to four‐fold coordination geometry around the metal center. Similarily, the salt [Li(DAD)2 ][Co(TMADS)3 ] was isolated which demonstrates an ion separated Co(II) anion with silylamide ligation and Li + counter cation. Transpyrrolylation using [Co(TMSA)2 ]2 was established for the synthesis of bis[N, N'‐2‐(dimethylaminomethyl)pyrrolyl]cobalt(II), and bis(N‐2‐( tert ‐butyliminomethyl)pyrrolyl)cobalt(II). Treatment of CoCl2 with two equivalents of lithiated N, N‐dimethyl(N'‐ tert ‐butyl)ethane‐1‐amino‐2‐amide and N, N‐dimethyl(N'‐trimethylsilyl)ethane‐1‐amino‐2‐amide resulted in the respective Co(II) amido‐amines. Reaction of CoCl2 with lithium 4‐methyl‐N‐(trimethylsilyl)pyridine‐2‐amide yielded the first binuclear, homoleptic Co(II) aminopyridinate complex with a distorted trigonal bipyramidal coordination environment (τ5 =0.533) for one central Co(II) ion and a weakly distorted tetrahedral coordination geometry (τ4 =0.845) for the other. All of the new compounds were thoroughly characterized in terms of composition and structure. Finally, the key thermal characteristics of volatility and thermal stability were assessed using a combination of thermogravimetric analysis and complementary bulk sublimation experiments. Abstract : A family of cobalt(II) complexes comprising amides, pyrrolates as well as aminopyridinates has been synthesized, structurally explored and evaluated with respect to their suitability as precursors for CVD/ALD applications. The effect of ligand choice and coordination environment on the thermal properties was examined, rendering cobalt(II) iminopyrrolates as promising precursor candidates.